The social protection of mobile populations (Revista LIDER, 2020)
This study analyzes mobile populations in Nicaragua in the context of Central American integration. The analysis reveals an emphasis on security in policies rather than a human rights approach. Likewise, the analysis suggests that the structural problems of the Central American states have impeded an integral policy of development and migration.